2017
DOI: 10.1002/adfm.201703140
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed All‐Fiber Li‐Ion Battery toward Wearable Energy Storage

Abstract: Conventional bulky and rigid power systems are incapable of meeting flexibility and breathability requirements for wearable applications. Despite the tremendous efforts dedicated to developing various 1D energy storage devices with sufficient flexibility, challenges remain pertaining to fabrication scalability, cost, and efficiency. Here, a scalable, low-cost, and high-efficiency 3D printing technology is applied to fabricate a flexible all-fiber lithium-ion battery (LIB). Highly viscous polymer inks containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
244
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(265 citation statements)
references
References 48 publications
1
244
0
Order By: Relevance
“…Direct ink writing (DIW) is one of the most commonly used 3D‐printing techniques. It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…Direct ink writing (DIW) is one of the most commonly used 3D‐printing techniques. It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…It has attracted greatly attention due to its good scalability, low cost and ability to complete complex work. Wang et al reported on a scalable, low‐cost and high‐efficiency three‐dimension printing technology to fabricate a flexible fibrous LIB using lithium iron phosphate as cathodes and lithium titanate as anodes . The electrode materials of LiFePO 4 and Li 4 Ti 5 O 12 were added together with the carbon nanotube conductive additive and added to the polyvinylidene difluoride solution to form cathode and anode inks for printing LiFePO 4 (cathode) and Li 4 Ti 5 O 12 (anode) fibers.…”
Section: Flexible Fibrous Lithium‐ion Batteriesmentioning
confidence: 99%
“…Generally, in Li-S battery system, the sulfur-based cathode can effectively lower the cost of devices, while its lithiated intermediate, soluble polysulfides are prone to make capacity degradation and decreased lifespan. [54] Copyright 2017, Wiley-VCH. Flexible, highly conducting and self-standing sulfur cathode were successfully prepared with activated carbon fiber cloth and template-synthesized CNT membranes, [56,57] blazing the direction for the realization of fiber-shaped Li-S battery.…”
Section: Lithium-sulfur Batterymentioning
confidence: 99%
“…Polyimide/CNT hybrid fiber; LiMn 2 O 4 /CNT hybrid fiber [49] In parallel 86 mAh g −1 at 600 C Can be woven into flexible battery textile Li 4 Ti 5 O 12 /CNT/PVDF and LiFP 6 /CNT/PVDF inks [54] Twisted 110 mAh g −1 at 50 mA g −1 Can be woven into fabric Lithium-sulfur battery CNT fiber incorporated with CMK-3/S; lithium wire [58] Cable type First discharge capacity of 1051 mAh g −1 at 0.1 C…”
Section: Conclusion and Perspectivementioning
confidence: 99%